2010
DOI: 10.1590/s1516-18462010005000140
|View full text |Cite
|
Sign up to set email alerts
|

Análise das habilidades auditivas de crianças com respiração oral

Abstract: OBJETIVO: destacar possíveis relações entre respiração oral e o sistema auditivo central de crianças em idade escolar, a partir da análise das habilidades auditivas de resolução temporal integração e separação binaural, atenção dividida, memória auditiva e fechamento auditivo. MÉTODOS: estudo em 102 escolares, entre 8 e 12 anos. Grupo I composto por 52 crianças com respiração oral e 50 crianças formaram o grupo II, com respiração nasal. Foram utilizados testes de Fala Filtrada, Teste de Padrões de Freqüência e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 7 publications
(9 reference statements)
0
21
0
5
Order By: Relevance
“…Mouth breathing is a multifactorial syndromeand is a health concern as it can lead to many problems such as: malocclusion, negative impact on oral health, affected speech, and hearing and quality of life . Its prevalence ranges from 50% to 60% in Brazil, and 71% globally, decreasing with age .…”
mentioning
confidence: 99%
“…Mouth breathing is a multifactorial syndromeand is a health concern as it can lead to many problems such as: malocclusion, negative impact on oral health, affected speech, and hearing and quality of life . Its prevalence ranges from 50% to 60% in Brazil, and 71% globally, decreasing with age .…”
mentioning
confidence: 99%
“…In one of them, the mouth breathers by functional etiology had 100% of normal hearing and in the others etiologies, a mild conductive hearing loss was prevalent, especially in cases of adenoid hypertrophy 33 . In the other study, children with MB showed lower performance on auditory processing skills than children with normal breathing pattern 34 .…”
Section: Hearing Changesmentioning
confidence: 70%
“…Extensive research, using the SSW test for evaluating AP, has been carried out on clinical populations assessing: difficulties in learning to read and write 1,4,[8][9][10][11] , the relationship between phonological disorder and AP [12][13][14][15][16][17][18] ; the relationship between oral breathing and the central auditory system 19 ; dyslexia 20 ; comorbidity between attention deficit hyperactive disorder (ADHD) and dyslexia 21 ; the relationship between performance in cognitive tests and AP tasks 22 ; listening skills in students aged 7 to 10 years, from different socioeconomic and cultural levels 23 and effectiveness of an informal program of specific auditory training for Auditory Processing Disorders (APD) in a group of 24 patients with this alteration.…”
Section: Methodsmentioning
confidence: 99%